Ways to combine the results of the analysis of employees activity of state authorities - Karkovska, Veronika; Yaremko, Iryna (Видавництво Львівської політехніки, 2017)
The article demonstrates a factor model of due performance of all norms and rules by officials in a governmental body. It singularizes the following basic indices of the factor model: index of official’s adherence to rules and norms and performance of them; index of adherence to rules and norms and performance of them during inspection in a governmental body by an employee of an organization, performing the inspection; index of safety of governmental bodies, covering the whole of statistic reporting regarding violations of this governmental body by an employee of an organization, performing the inspection; index of safety of governmental bodies, covering the whole of statistic reporting regarding violations of this governmental body. It substantiates the opportunity of using the factor model for assessment of governmental officials’ activityresults.
Keywords: Governmental bodies; assessment of officials’ activity results; factor model; official’s adherence to rules and norms and performance of them; level of knowledge; level of violations